If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -5x = 72 Reorder the terms: 3(4 + x) + -5x = 72 (4 * 3 + x * 3) + -5x = 72 (12 + 3x) + -5x = 72 Combine like terms: 3x + -5x = -2x 12 + -2x = 72 Solving 12 + -2x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2x = 72 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 72 + -12 -2x = 72 + -12 Combine like terms: 72 + -12 = 60 -2x = 60 Divide each side by '-2'. x = -30 Simplifying x = -30
| 65+900+b=1053 | | 5.87b=8.68+3.68b | | (19-X)-(18-X)=3 | | 16=4(x-2) | | n^2-10n-88=8 | | 3(5-x)=2(1+x) | | 6y=5x+60 | | 4x^2-17x+34=6x+6 | | 2n^2+5n-33=12 | | 19x-18x=3 | | x+3x+3x+5=166 | | 3(m+4)=-24-m | | 10-2x=20x+4 | | log(x-11)+log(x-8)=1 | | 23-13y=10y | | -16t^2+69t+3=0 | | 15p+16q+p-6q-3p= | | x+x+22=460 | | 8x+5x+3+7=7x+4+5x | | 41x-96=41 | | n^2-11n-42=0 | | log(x-3)=4 | | 23x-13y=10y | | 2b+3=-8 | | 1.5(3)+2y=8 | | 10y+45=135 | | (9b-2)-2(4b+3)=-3 | | 6b^2+b-26=0 | | Logy=1.111152 | | e^1=10.5 | | (2y^2-5y+4)-(3y^2-5y+8)= | | 0.1f+1=0.01f+10 |